Time for a Western Australian ‘Group of Three’? A speculative essay - Turner, Michael; Brown, Alistair (National Tertiary Education Union, 2015)
This study analyses the theoretical cost-savings that might flow from a merger of three of Western Australia’s five universities. The results of the study show that an amalgamation would not only reduce costs of operation, but also improve non-current asset use and accountability. Combination reporting also allows the key stakeholders to appraise these universities’ main financial activities, which appear to be maintaining a relatively high level of non-salary expenditure as a percentage of revenue and preserving a very high percentage of land and buildings as mainstay assets.